Interaction of the Hsp90 cochaperone cyclophilin 40 with Hsc70 - Carrello, Amerigo (Cell Stress Society International, 2004)
The high-affinity ligand-binding form of unactivated steroid receptors exists as a multicomponent complex that includes heat shock protein (Hsp)90; one of the immunophilins cyclophilin 40 (CyP40), FKBP51, or FKBP52; and an additional p23 protein component. Assembly of this heterocomplex is mediated by Hsp70 in association with accessory chaperones Hsp40, Hip, and Hop. A conserved structural element incorporating a tetratricopeptide repeat (TPR) domain mediates the interaction of the immunophilins with Hsp90 by accommodating the C-terminal EEVD peptide of the chaperone through a network of electrostatic and hydrophobic interactions. TPR cochaperones recognize the EEVD structural motif common to both Hsp90 and Hsp70 through a highly conserved clamp domain. In the present study, we investigated in vitro the molecular interactions between CyP40 and FKBP52 and other stress-related components involved in steroid receptor assembly, namely Hsp70 and Hop. Using a binding protein-retention assay with CyP40 fused to glutathione S-transferase immobilized on glutathione-agarose, we have identified the constitutively expressed form of Hsp70, heat shock cognate (Hsc)70, as an additional target for CyP40. Deletion mapping studies showed the binding determinants to be similar to those for CyP40-Hsp90 interaction. Furthermore, a mutational analysis of CyP40 clamp domain residues confirmed the importance of this motif in CyP40-Hsc70 interaction. Additional residues thought to mediate binding specificity through hydrophobic interactions were also important for Hsc70 recognition. CyP40 was shown to have a preference for Hsp90 over Hsc70. Surprisingly, FKBP52 was unable to compete with CyP40 for Hsc70 binding, suggesting that FKBP52 discriminates between the TPR cochaperone-binding sites in Hsp90 and Hsp70. Hop, which contains multiple units of the TPR motif, was shown to be a direct competitor with CyP40 for Hsc70 binding. Similar to Hop, CyP40 was shown not to influence the adenosine triphosphatase activity of Hsc70. Our results suggest that CyP40 may have a modulating role in Hsc70 as well as Hsp90 cellular function.